TRANSLATION OF PHRASAL VERBS INTO INDONESIAN - Maharani Santika, I Dewa Ayu Devi; Widiadnya Putri, I Gusti Vina; Suastini, Ni Wayan (Lingual Journal of Language and Culture; Vol 4 No 2 (2017)DO - 10.24843/LJLC.2017.v04.i02.p03, 2017)
This study has two aims, those are to analyze: (1) the classification of phrasal verbs found in a short story and the classification of their translations in Indonesian done by some English teachers from some primary schools in Denpasar, and (2) how the meaning of phrasal verbs in SL help to determine their equivalents in TL. The classification and the meaning of phrasal verbs are proposed by McArthur and Atkins (1975). Based on the analysis there were three categories of 34 phrasal verbs found in the data source, those are: intransitive verbs, transitive separable verbs, and transitive fused verbs. The results found that most of the phrasal verbs are included into transitive separable verbs and from the three categories of phrasal verbs; they were translated mostly into transitive verbs. Meanwhile, the meanings of phrasal verbs in SL determine the suitable equivalents for the phrasal verbs in TL since there were variants equivalents given in the translations. Keywords: Phrasal verbs, Translation, Words meaning